2020
DOI: 10.1097/md.0000000000019379
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay for a quality-adjusted life year among advanced non-small cell lung cancer patients in Viet Nam, 2018

Abstract: To examine the willingness to pay (WTP) for a quality-adjusted life year (QALY) gained among advanced non-small cell lung cancer (NSCLC) patients in Viet Nam and to analyze the factors affecting an individual's WTP. A cross-sectional, contingent valuation study was conducted among 400 NSCLC patients across 6 national hospitals in Viet Nam. Self-reported information was recorded from patients regarding their socio-demographic status, EQ-5D (EuroQol-5 dimensions) utility, EQ-5D vas, and WTP for 1 QALY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
2
13
1
Order By: Relevance
“…The median 99,906 RMB (14,479USD, 1.39 times the GDP per capita) of the overall sample in our study was smaller than the National Institute for Health and Care Excellence (NICE) threshold for end-of-life interventions of £50,000 (64,103USD, 1.56 times the GDP per capita in 2020) [ 27 ], and the ratio of the GDP per capita was close. In comparison to the WTP/QALY for patients with malignant tumors in other Asian countries, the median 99,906 RMB (14,479USD, 1.39 times the GDP per capita) of the overall sample in this paper was between the 11,031USD among patients with lung cancer in Vietnam in 2018 [ 28 ] and the 19,200–32,000USD among patients with solid tumors and the general population in the Kingdom of Saudi Arabia [ 29 ]. However, the ratio of the median WTP/QALY value to China’s GDP per capita was lower than the ratio of that in Vietnam (4.4 times the GDP per capita in 2017) [ 28 ] and close to that in Saudi Arabia (1–1.5 times the GDP per capita) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median 99,906 RMB (14,479USD, 1.39 times the GDP per capita) of the overall sample in our study was smaller than the National Institute for Health and Care Excellence (NICE) threshold for end-of-life interventions of £50,000 (64,103USD, 1.56 times the GDP per capita in 2020) [ 27 ], and the ratio of the GDP per capita was close. In comparison to the WTP/QALY for patients with malignant tumors in other Asian countries, the median 99,906 RMB (14,479USD, 1.39 times the GDP per capita) of the overall sample in this paper was between the 11,031USD among patients with lung cancer in Vietnam in 2018 [ 28 ] and the 19,200–32,000USD among patients with solid tumors and the general population in the Kingdom of Saudi Arabia [ 29 ]. However, the ratio of the median WTP/QALY value to China’s GDP per capita was lower than the ratio of that in Vietnam (4.4 times the GDP per capita in 2017) [ 28 ] and close to that in Saudi Arabia (1–1.5 times the GDP per capita) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to the WTP/QALY for patients with malignant tumors in other Asian countries, the median 99,906 RMB (14,479USD, 1.39 times the GDP per capita) of the overall sample in this paper was between the 11,031USD among patients with lung cancer in Vietnam in 2018 [ 28 ] and the 19,200–32,000USD among patients with solid tumors and the general population in the Kingdom of Saudi Arabia [ 29 ]. However, the ratio of the median WTP/QALY value to China’s GDP per capita was lower than the ratio of that in Vietnam (4.4 times the GDP per capita in 2017) [ 28 ] and close to that in Saudi Arabia (1–1.5 times the GDP per capita) [ 29 ]. In comparison to other studies that were based on the hypothetical scenario of incurable and maintenance therapy “restore and maintain in full health but need continuous administration”.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported a range of 20-50% of advanced NSCLC patients without tissue biopsy (8,19). In addition, previous clinical studies consistently reported that stage IIIB or IV adenocarcinoma is the dominant histology (>80%) among Vietnamese NSCLC patients (30,31). Thus, despite of the missing histology information, we believed that the patients in both cohorts had comparable histology features with majority had advanced adenocarcinoma, minimizing the confounding effect of histology information to our comparison.…”
Section: Discussionmentioning
confidence: 91%
“…For studies using CV method, only 3/24 (12.5%) studies [45,61,66] were considered of high quality, 13/24 (54.2%) were of moderate quality [46,55,58,59,62,64,68,71,73,76,[79][80][81], and 8/24 (33.3%) [47,54,56,60,63,67,70,77] were of low quality. Majority of the CV studies lacked information on test for validity and reliability, with only 50% and 16.7% of the studies reporting on validity and reliability test, respectively.…”
Section: Quality Assessmentmentioning
confidence: 99%